(untitled) (Journal of Forensic Medicine & Toxicology, 2011)
The present study was a cross sectional study carried out in a tertiary care service hospital of Pune, which caters mainly armed forces persons and civilian population living in and around cantonment area. Cases for the present study include mainly retrospective and few prospective cases. A total of 113 cases of induced abortions were studied during the above-mentioned period. Maximum incidence of induced abortion was seen in the age group 25-35 years (n=71, 62.8%) followed by age group 15-25 yrs (n=37, 32.7%) and 35-45 yrs (n=5, 4.4%). Majority of women seeking abortion in the study were hindu (n=103, 91%) followed by Muslim (n=6, 5.3%), Sikhs (n=3) and Christian (n=1).Maximum women reported for abortion during 6-12 weeks (n=71, 62.8%), followed by less than 6 weeks (n=23, 20.4%) and 12-20 weeks (n=14, 12.4%). Majority of abortion seekers in the study had parity two (n=46, 40.7%) followed by parity one (n=22, 19.5%) and primigravida (n=19, 16.8%). Planned Parenthood (n=81, 71.7%) was the most common reason for seeking abortion by women. Cervical dilatation followed by suction and evacuation (n=84, 74.3%) was the most common method employed for inducing abortion, followed by misoprostol suppositories (n=18, 15.9%) dilatation and curettage (n=8, 7%) and menstrual regulation (n=3, 2.7%).